ANALISIS LINGUISTIK TERHADAP LIRIK LAGU “EVALUASI” KARYA HINDIA: KAJIAN SEMANTIK DALAM BAHASA INDONESIA - Gendis Sartika; Adellia Candra Maulana; Indira Pratama Julia Putri; Adinda Putri Widianita (Jurnal PENEROKA, 2026)
This study aims to identify and describe the types of semantic meanings found in the lyrics of Evaluasi by Hindia. A qualitative descriptive approach with semantic analysis was employed. The data consisted of words, phrases, and sentences containing lexical, connotative, contextual, and ambiguous meanings. Data were collected through documentation and note-taking techniques and analyzed using content analysis based on semantic theory. The findings indicate that the lyrics are predominantly characterized by connotative meanings representing life experiences, self-reflection, and self-acceptance through the use of metaphors and expressive diction. In addition, lexical, contextual, and ambiguous meanings were identified, each contributing to the overall interpretation of the song. The predominance of connotative meaning demonstrates Hindia's use of figurative language to convey profound emotional messages while allowing multiple interpretations by listeners. These findings suggest that song lyrics function not only as entertainment but also as a meaningful linguistic medium that reflects human experiences. This study contributes to semantic studies, particularly in the analysis of meaning in song lyrics, and may serve as a reference for future research in linguistics and literary studies.